IDENTIFIKASI FAKTOR PENENTU PROFITABILITAS BPR DI PROVINSI NUSA TENGGARA TIMUR (NTT) - Saputri, Kristiani Hilda; Al Muizzuddin Fazaalloh (Contemporary Studies in Economic, Finance and Banking, 2024)
This study aims to determine the effect of CAR, LDR, and NPL on the profitability of Rural Banks in East Nusa Tenggara Province for the period 2017 – 2022. The purpose of this study is to determine the effect of capital adequacy, credit risk, liquidity risk, and operating costs on BPR profitability with a research sample of 11 banks. The research method used in this research is purposive sampling method. The data analysis technique uses panel data regression with a random effect model.